Factors Affecting Adoption of Improved Crops by Rural Farmers in Niger - Bago, Jean-Louis; Koutaba, Aude; Valéa, Aristide (My University, 2018)
Improved crops are advocated to meet the dual challenge of food security and the fight against poverty in developing countries. As most poor people in developing countries live in rural areas and depend on agriculture for their livelihood, an important key to get them out of poverty is to increase agricultural productivity by using technologies such as improved crops. However, the rate of improved crops adoption remains surprisingly low in Niger, one of the world poorest countries. In this paper, we examine the factors affecting adoption of improved crops by rural farmers focusing on Niger. Using the 2014’s National Survey on Households Living Conditions and Agriculture, we investigate the effect of farmers’ socioeconomic characteristics, the farm’s quality, the geographic location, the production system, the access to improved seeds and the land tenure on the probability to use improved crops rather than local crops. Our results suggest that the ownership of a government land title is the most important driver in the adoption of improved crops by rural farmers. In addition, being a female, educated, practicing polyculture, having access to improved seed increase the probability to adopt improved crops. In contrast, household size, operating on the parcel for a long period and the parcel size reduces the probability to use improved crops. These determinants of improved crops adoption should be considered in Niger’s agricultural policy to succeed in the dissemination of improved crops among rural farmers.
Supplemental Materials: https://osf.io/6p28d/
Keywords: Adoption; Improved crops; Farm; Farmer; Niger